The Essence of Worldly Life in Q.S. Al-Ḥadīd (57): 20 (An Analysis Using Michael Riffaterre’s Heuristic and Hermeneutic Reading) - Ahmad Hizkil (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
This study aims to reveal the the essence of world life described in Q.S Al Hadid (57): 20 based on Michael RIffaterre's heuristic and hermeneutic reading. This research is included in the descriptive-qualitative research by making Q.S Al Hadid (57): 20 as the object of research as well as the source of the data. The theory used is Michael Riffaterre's semiotic theory which introduces heuristic and hermeneutic reading methods in interpreting a text. The data collection technique is a listening and note-taking technique. Meanwhile, the data analysis technique is descriptive-analytic. The results of this study indicate that the parable of the world mentioned in Q.S. Al Hadid (57): 20 is the essence of the real life of the world. That the life of this world is just a game and a negligent joke. The parables of the world are a form of displacing of meaning as in Riffaterre's theory. The regularity of the editors in every parable of the world is a picture of the phase of human life from childhood to adulthood and then death. This meaning is part of the form of creating meaning. The prioritization of "forgiveness" over "pleasure" turns out to have its own meaning and it is also included in the form of creating of meaning